Menhaden Oil Decreases High-Fat Diet–Induced Markers of Hepatic Damage, Steatosis, Inflammation, and Fibrosis in Obese Ldlr(−/−) Mice - Depner, Christopher M. (American Society for Nutrition, 2012)
The frequency of nonalcoholic fatty liver disease (NAFLD) and nonalcoholic steatohepatitis (NASH) has increased in parallel with obesity in the United States. NASH is progressive and characterized by hepatic damage, inflammation, fibrosis, and oxidative stress. Because C20–22 (n-3) PUFA are established regulators of lipid metabolism and inflammation, we tested the hypothesis that C20–22 (n-3) PUFA in menhaden oil (MO) prevent high-fat (HF) diet–induced fatty liver disease in mice. Wild-type (WT) and Ldlr(−/−) C57BL/6J mice were fed the following diets for 12 wk: nonpurified (NP), HF with lard (60% of energy from fat), HF–high-cholesterol with olive oil (HFHC-OO; 54.4% of energy from fat, 0.5% cholesterol), or HFHC-OO supplemented with MO (HFHC-MO). When compared with the NP diet, the HF and HFHC-OO diets induced hepatosteatosis and hepatic damage [elevated plasma alanine aminotransferase (ALT) and aspartate aminotransferases] and elevated hepatic expression of markers of inflammation (monocyte chemoattractant protein-1), fibrosis (procollagen 1α1), and oxidative stress (heme oxygenase-1) (P ≤ 0.05). Hepatic damage (i.e., ALT) correlated (r = 0.74, P < 0.05) with quantitatively higher (>140%, P < 0.05) hepatic cholesterol in Ldlr(−/−) mice fed the HFHC-OO diet than WT mice fed the HF or HFHC-OO diets. Plasma and hepatic markers of liver damage, steatosis, inflammation, and fibrosis, but not oxidative stress, were lower in WT and Ldlr(−/−) mice fed the HFHC-MO diet compared with the HFHC-OO diet (P < 0.05). In conclusion, MO [C20–22 (n-3) PUFA at 2% of energy] decreases many, but not all, HF diet–induced markers of fatty liver disease in mice.